IMPLEMENTASI MODEL CREATIVE PROBLEM SOLVING UNTUK MENINGKATKAN PRESTASI PEMBELAJARAN PANCASILA DI SDN 29 DADOK TUNGGUL HITAM PADANG : Bahasa Indonesia - Nursi, M.; Darwianis, Darwianis; Pebriyenni, Pebriyenni; Sayuti, M.; Rachmana N, Mogastra (Cerdas Proklamator, 2025)
The low achievement of Pancasila learning in Phase C (Grade V) of the Odd Semester of the 2024-2025 Academic Year, in the Sub-element material "Forms of norms, rights, and obligations in their position as family members, school members, and citizens" is shown by an average learning outcome of 65.30 with a learning completion of 43.75%. After taking solution actions, namely by implementing the Creative Problem Solving learning model, this Classroom Action Research (CAR) has been able to overcome the problem of low student learning outcomes, namely increasing Pancasila learning achievement after going through two learning cycles, namely cycles I and II. With data collection using test instruments and data analysis using a quantitative descriptive analysis model. With a fairly high Learning Objective Completion Criteria (LOCC), namely the average minimum student score of 75 with a minimum learning completion percentage of 80%. After going through the learning process actions, an improvement achievement was obtained, namely from the initial data to cycle II showing learning completeness achievement of 35% increasing to 76.72% in cycle I, and increasing again to 83.19% in cycle II. This proves that the implementation of the creative problem solving learning model can effectively improve Pancasila learning achievement in class VIII.6 students of SD Negeri 29 Dadok Tunggul Hitam, Padang City in the odd semester of the 2024/2025 academic year.